Find the solution(s) of 3(x^2)-6x+2=0

This is a quadratic equation and as such it has zero, one or two solutions depending on the value of the discriminant (b2-4ac). In this equation, a=3, b=-6 and c=2 so b2-4ac = 36-24=12. As this is >0 the equation has two real solutions, however this is not a square number and therefore we cannot factorise and will have to use the quadratic formula. This is (-b (+/-) (b2-4ac)1/2)/(2a). Subsituting in a, b and c gives us (6 (+/-) 121/2)/6 which means our two solutions are x=1+(1/6)121/2and x=1-(1/6)121/2

Answered by Angus S. Maths tutor

3663 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Do the following vector equations intersect? l = (1 + μ)i + (2 - μ)j + (2μ - 5)k, and m = 2λi + 3j + (2 + λ)k.


Given that z=sin(x)/cos(x), show that dz/dx = sec^2(x).


A curve has the equation x^2 +2x(y)^2 + y =4 . Find the expression dy/dx in terms of x and y [6]


Differentiate sin3x-3x= f(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences